Case Report: Metagenomic Next-Generation Sequencing for Diagnosis of Human Encephalitis and Endophthalmitis Caused by Pseudorabies Virus - Yan, Weiqian; Hu, Zhiping; Zhang, Yingchi; Wu, Xiaomei; Zhang, Hainan (Frontiers in Medicine, 2022)
Purpose The objective of our study was to report a case of encephalitis and endophthalmitis caused by pseudorabies virus (PRV), identified using metagenomic next-generation sequencing (mNGS). Case Presentation A 54-year-old worker, from a swine slaughterhouse, developed signs of severe encephalitis, including fever, disturbance of consciousness, hypopnea, and status epilepticus, after finger injury at work. The PRV sequences were successfully identified from the blood, cerebrospinal fluid (CSF), and aqueous humor of the patient through mNGS, which was further verified using a Sanger sequencing. Conclusion Our case emphasizes the importance of mNGS in early diagnoses of infectious diseases, and gives a clue that PRV can spread across species and infect human. It is necessary to carry out a skin protection and education about disease prevention for people who have close contact with swine.